Politics, markets and social concerns: liberalisation and reorganisation of space - Arora, Dolly (1996)
To comprehend complexity of shifting relationship between politics, market and social concerns under SAP, the author focuses on its reorganisation of political space, reorientation of economy and redefinition of social concerns. With a people-centred perspective, she critically examines the prevailing misconceptions on inherent possibilities of liberalisation and explores appropriateness and scope of alternative approaches towards addressing social concerns. - Reproduced
Keywords: Liberalization - India; Economic liberalization